2008
DOI: 10.1017/s0022215108003770
|View full text |Cite
|
Sign up to set email alerts
|

Randomised, double-blinded, placebo-controlled, clinical trial of ozone therapy as treatment of sudden sensorineural hearing loss

Abstract: Ozone therapy is a significant modality for treatment of sudden sensorineural hearing loss; no complications were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
4
1
3
Order By: Relevance
“…At variance with our results, Ragab et al ( 2009 ), after performing a trial in 45 patients with sudden sensorineural hearing loss, by using a reduced volume (100 ml) of major AHT obtained 77% recovery against 40% in placebo control, infused with distilled water!!! The discrepancy may be due to the fact that in these Egyptians patients the hearing loss was acute but nonetheless we critized their imprecise ozonetherapeutic methodology (Bocci et al, 2009e ) and therefore further clinical studies are necessary.…”
Section: The Problems Of Tinnitus and Sudden Hearing Loss (Shl) Is Ocontrasting
confidence: 77%
“…At variance with our results, Ragab et al ( 2009 ), after performing a trial in 45 patients with sudden sensorineural hearing loss, by using a reduced volume (100 ml) of major AHT obtained 77% recovery against 40% in placebo control, infused with distilled water!!! The discrepancy may be due to the fact that in these Egyptians patients the hearing loss was acute but nonetheless we critized their imprecise ozonetherapeutic methodology (Bocci et al, 2009e ) and therefore further clinical studies are necessary.…”
Section: The Problems Of Tinnitus and Sudden Hearing Loss (Shl) Is Ocontrasting
confidence: 77%
“…Some studies have indicated that SSHL develops when the inner ear does not receive a sufficient oxygen supply [18]. Consequently, hyperbaric oxygen treatment has been used as an alternative option for the treatment of SSHL [19,20]. At Kyoto University Hospital, hyperbaric oxygen therapy has been used as a secondary treatment of choice for glucocorticoid-resistant SSHL [14].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Ragab et al 26 comprising 45 patients with ISSNHL at Menoufiya University Hospital (Egypt) between 2004 and 2006, the study group (30 patients) was administered ozone therapy through the autohemotherapy method, while the placebo group (15 patients) received sterile distilled water infusions. Both of the patient populations/groups received 10 session treatments twice a week.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these features, ozone therapy increases antioxidant efficiency and becomes effective for the treatment of ISSNHL by impacting cellular stress. 26 …”
Section: Discussionmentioning
confidence: 99%